Study on Creativity Potential of Scheduled Cast Students With Ref to Five Sub-Tests of Language Creativity: Exploring Creativity Potential in Scheduled Cast Students (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Fluency is the ability of person to produce number ofrelevant and unrepeated ideas. Relevance is judged on the basis of theappropriateness of the response when considered in relation to the test problemand an unrepeated idea is one which has been expressed only once under givenproblem.